The mechanical career of Councillor Orffyreus, confidence man - Jenkins Villalobos, Alejandro (2013)
In the early 18th century, J. E. E. Bessler, known as Orffyreus, constructed several wheels that he claimed could keep turning forever, powered only by gravity. He never revealed the details of his invention, but he conducted demonstrations (with the machine's inner workings covered) that persuaded competent observers that he might have discovered the secret of perpetual motion. Among Bessler's defenders were Gottfried Leibniz, Johann Bernoulli, Professor Willem 's Gravesande of Leiden University (who wrote to Isaac Newton on the subject), and Prince Karl, ruler of the German state of Hesse-Kassel. We review Bessler's work, placing it within the context of the intellectual debates of the time about mechanical conservation laws and the (im)possibility of perpetual motion. We also mention Bessler's long career as a confidence man, the details of which were discussed in popular 19th-century German publications, but have remained unfamiliar to authors in other languages.